2007
DOI: 10.1093/nar/gkm171
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the DNA binding and bending capacities and the oligomeric states of the immunity repressors of heteroimmune coliphages P2 and W 

Abstract: Bacteriophages P2 and WΦ are heteroimmune members of the P2-like family of temperate Escherichia coli phages. Temperate phages can grow lytically or form lysogeny after infection. A transcriptional switch that contains two con-vergent promoters, Pe and Pc, and two repressors regulate what life mode to enter. The immunity repressor C is the first gene of the lysogenic operon, and it blocks the early Pe promoter. In this work, some characteristics of the C proteins of P2 and WΦ are compared. An in vivo genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The number of C proteins in the respective complex is not known, but the SPR analysis does not indicate a higher number of C proteins per DNA molecule for P2 Hy dis C. A genetic analysis of the P2 C and Wϕ C proteins has shown that in the absence of DNA they form dimers, but not higher oligomeric structures (8). During gel-filtration all C proteins elute at the same positions, indicating also that P2 Hy dis C is a dimer in solution (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of C proteins in the respective complex is not known, but the SPR analysis does not indicate a higher number of C proteins per DNA molecule for P2 Hy dis C. A genetic analysis of the P2 C and Wϕ C proteins has shown that in the absence of DNA they form dimers, but not higher oligomeric structures (8). During gel-filtration all C proteins elute at the same positions, indicating also that P2 Hy dis C is a dimer in solution (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the complexes formed by P2 C and Wϕ C may indicate that they form similar complexes, but in the case of P2 there is no difference in the affinity to one half-site compared to the other. Using a circular permutation assay, the P2 and Wϕ C proteins have been shown to bend their respective DNA targets upon binding, and Wϕ C as opposed to P2 C is able to bind to only one half-site (8). This may explain why three retarded bands can be detected with Wϕ C but only two with P2 C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The P2 C-repressor forms very stable dimers, but not higher oligomers in the absence of DNA (Ahlgren-Berg et al 2007). Earlier studies, however, have shown that the P2 C-repressor might bind as dimers to each half site and then form tetramers, which can be seen as four protected regions in a foot-print analysis.…”
mentioning
confidence: 92%